The Impact of Age and Nutritional Status on Wound Healing After Caesarean Section - Zahroh, Manzilatuz; Pujiastuti, Nurul; Nataliswati, Tri; Solikhah, Fitriana Kurniasari (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2024)
Age and nutritional status are crucial in wound healing after a caesarean section. This study explores the relationship between these two factors and the duration of wound healing post-surgery at the Islamic University Hospital of Malang. Using a cross-sectional research design, the investigation will include all patients who had caesarean sections between March and May 2024, totalling around 31 respondents. The sampling technique employed for this study was total sampling. The Spearman Rank test was used to assess the data for statistical analysis. Findings show that 71% of respondents are in a non-risk age group, and 64.5% have good nutritional status. Conversely, 64.5% experienced poorly healing wounds. The Spearman Rank test produced a p-value of 0.005, indicating a significant relationship between age and wound healing duration, and a p-value of 0.000 showed a significant association between nutritional status and healing length. Correlation coefficients of 0.489 and 0.607 indicate moderate positive correlations. In conclusion, the study establishes relationships between age, nutritional status, and wound healing duration post-caesarean section, suggesting that future research should investigate other influencing factors like medical history and surgical complications.